Dog Man: Grime and Punishment - Book 9 Grime and punishment - Pilkey, Dav 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2020)
"The Supa Buddies bamboozled the baddies, but all's not right in the world. Dog Man has a new problem to pound, and he's going to need his entire pack to help him. Will he go barking up the wrong tree?"--Provided by publisher.
Keywords: Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Comic books, strips, etc -- United States; Dogs -- Fiction; Police -- Fiction; Cats -- Fiction; Good and evil -- Fiction; Cartoons and comics; Humorous Stories; Action and adventure comics; Humorous comics; Graphic novels; Comics (Graphic works)